1991
DOI: 10.1007/bf00928685
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Western blotting procedure for the immunodiagnosis of human toxocariasis

Abstract: To improve the immunodiagnosis of human toxocaral disease, a sensitive and specific assay using the Western blotting procedure (WB) with excretory-secretory antigens from Toxocara canis larvae (TES) was developed and compared with the standard enzyme-linked immunosorbent assay method (TES-ELISA) using the same antigens. We tested groups of sera from laboratory animals or patients presenting with toxocariasis or other helminthic diseases and a group of sera from people dwelling in an area endemic for toxocarias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
169
1
9

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(188 citation statements)
references
References 21 publications
9
169
1
9
Order By: Relevance
“…The MWs of these components are 24,28,30,35,48,56,67,117,136 and 152 kDa. Four of these antigens bands correlate perfectly with LMW bands described by Magnaval et al (1991).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The MWs of these components are 24,28,30,35,48,56,67,117,136 and 152 kDa. Four of these antigens bands correlate perfectly with LMW bands described by Magnaval et al (1991).…”
Section: Discussionsupporting
confidence: 60%
“…As revealed by western blot, there are two main groups of bands present in the positive cases: one of 24-45 kDa and another group of 66-200 kDa (Magnaval et al 1991, Nunes et al 1997, Morales et al 2002. These studies suggest the HMW bands can cause cross-reactivity and the LMW bands would be more specific for Toxocara.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…MAGNAVAL et al 67 used the WB technique to confirm positivity determined in human sera previously processed by the ELISA technique for IgG antibodies using antigen TES and achieved greater specificity with fractions of low molecular weight (24 to 35 kDa). The study by NUNES et al 78 , using the Immunoblot test, determined that the 55-66 kDa antigenic complex was responsible for the cross reactivity between T. canis and A. suum; whereas LYNCH et al 66 had stated that strong cross reactivity between these two ascarids occurred in the 81 kDa antigen.…”
Section: Immunoblottingmentioning
confidence: 99%
“…In our laboratory the immunodiagnosis of trichinellosis is performed by using an enzyme-linked immunosorbent assay (ELISA) in which the excretory/secretory (ES) products of Trichinella spiralis muscle larvae are used as antigen (van Knapen et al, 1982 (Magnaval et al, 1991;Gadea et al, 1999). We observed that the IgG4 response directed to a 45 kDa component of ES products of muscle larva was Trichinella-specific.…”
mentioning
confidence: 99%